PERSEPSI MASYARAKAT TERHADAP PERTUNJUKAN ORGAN TUNGGAL MALAM HARI DALAM ACARA PERNIKAHAN DI TEBO - Wulan Larasaty; Marzam Marzam; Syeilendra Syeilendra (FBS Universitas Negeri Padang, 2013)
Abstract The purpose of thisd research is examine the perception of the society towards the evening keyboard show (organ tunggal) held at a wedding party. This research was a descriptive qualitative one. The data were collected through an observasion, interviews, a library based research, photographs, and reconrdings. The result of this research showed that the society in general had a positive perception towards the show including the keyboardist and the party hlder. Tha show is regarded as free and fun entertainment which provides a place for the youth to garher and a side job for the keyboardist or the singer to do however. Negative perception towards the show was raised among people enganged in religious parties and the society figures. For them, the evening keyboard show is not a goog deed to watch, it is an evil thing indeed. Kata kunci : persepsi, masyarakat, organ tunggal, pernikahan